مصطلحات "التصوير" و"التمثيل" و"التخييل" عند الزمخشري في "الكشاف" = Mustalahat "al-taswir" wa "al-tamthil" wa 'al-takhyil" 'inda al-Zamakhshari fi "al-Kashaf" - Daud, Nadwah (Edinburgh University Press, 2008)
This study explores the terminology of al-taṣwīr (‘imagery’), al-tamthīl (‘representations’) and al-takhyīl (‘imagination’) in al-Zamakhsharī’s al-Kashshāf. It first explores the meanings of the terms themselves, and then moves on to discuss their roles in elucidating the underlying signification of the Qur'anic text. Al-Zamakhsharī regards taṣwīr, tamthīl and takhyīl as indispensable exegetical tools, the primary function of which is clarification and explanation. After analysing the meaning of these three terms, this article also considers al-Zamakhsharī’s commentary on the Qur'anic text